Performance evaluation of PACT Pilot-plant for CO2 capture from gas turbines with Exhaust Gas Recycle. (April 2016) - Akram, M.; Ali, U.; Best, T.; Blakey, S.; Finney, K.N.; Pourkashanian, M.
Highlights: Impact of gas turbine exhaust gas circulation on capture plant is evaluated. Absorber performance at varying CO2 concentrations is evaluated. Stripper energy balance is performed for steam generation and condenser duty. The impact of cross exchanger approach temperature on reboiler duty is evaluated. The plant is modelled using new Acid Gas property package in Aspen HYSYS. Abstract: Exhaust Gas Recycle (EGR) is one of the technologies used to increase the CO2 concentration in the gas turbine flue gas. This paper presents the results of an experimental campaign carried out at the Pilot-scale Advanced Capture Technology (PACT) facilities at the UK Carbon Capture and Storage Research Centre (UKCCSRC). A 100 kWe Turbec T100 PH microturbine was integrated with a post combustion CO2 capture plant that has a CO2 capture capacity of one ton per day. The impact of different CO2 concentrations (representing a range of EGR ratios) on the post-combustion CO2 capture process was experimentally evaluated using 30% (wt.%) Monoethanolamine (MEA) solvent. It was observed that the specific reboiler duty was reduced by around 7.1% per unit percentage increase in CO2 concentration. Overall, it was seen that the higher the CO2 concentration, the lower the specific reboiler duty at a fixed capture rate. Both rich and lean solvent loadings increased with increase in flue gas CO2 concentration. Energy balance on the stripper has shown that steam generation rate and condenser duty increases with increase in CO2 concentration. The experimental data was used to develop and validate the model for the Pilot-scale amine capture plant using Aspen HYSYS.